Penolakan Parlemen Inggris Terhadap Kebijakan Backstop Irlandia - Indriastuti, Suyani; Lowirani, Stefania; Soelistijono, Pra Adi (Electronical Journal of Social and Political Sciences (E-SOSPOL), 2022)
The Irish Backstop is a protocol in the 2018 (rejected) draft of the Withdrawal Agreement, which would leave the UK (in general) in the EU Customs Union and Northern Ireland (in particular) in some aspects of the European Single Market, until a solution is found to prevent hard borders. The aim is not to compromise the Good Friday Agreement and to maintain the integrity of the European Single Market. It will enter into force only if no other solution exists by the end of the (agreed upon) transition period, and will remain in effect until such a solution is found and agreed to be practical. However, the backstop policy was rejected by the British Parliament which resulted in the resignation of Theresa May as British Prime Minister. By using constructivism and postfunctionalism theory, the author analyzes the reasons for the British Parliament's rejection of the Backstop Policy.